2016
DOI: 10.3892/mmr.2016.5474
|View full text |Cite
|
Sign up to set email alerts
|

The effect of LOXL2 in hepatocellular carcinoma

Abstract: Lysyl oxidase-like 2 (LOXL2) is key in the hepatocellular carcinoma (HCC) tumor microenvironment and metastatic niche formation. However, its effect on proliferation and clinical parameters in HCC require further elucidation. The present study aimed to investigate LOXL2 expression in HCC from in vitro and clinical aspects. The present study constructed LOXL2-small interfering RNA with a lentiviral vector, investigated the effect of LOXL2 on proliferation using HCC cell lines via a series of assays, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Other researchers and we have demonstrated that the expression of LOXL4 is upregulated in several human cancers, including head and neck squamous cell carcinoma (HNSCC) [47], laryngeal squamous cell carcinoma [49], and gastric cancer [11]. Others have shown that LOXL2 is frequently overexpressed in human HCC [50, 51], and we showed that LOXL4 expression was also increased at both mRNA and protein levels in HCC. Furthermore, we found that LOXL4 upregulation was significantly correlated with tumor differentiation, vascular invasion, and TNM stage and predicted a poor prognosis, in contrast to a previous study demonstrating that LOXL4 is downregulated in HCC tissues, and the downregulation is correlated with aggressive tumors and a worse clinical outcome [12].…”
Section: Discussionsupporting
confidence: 52%
“…Other researchers and we have demonstrated that the expression of LOXL4 is upregulated in several human cancers, including head and neck squamous cell carcinoma (HNSCC) [47], laryngeal squamous cell carcinoma [49], and gastric cancer [11]. Others have shown that LOXL2 is frequently overexpressed in human HCC [50, 51], and we showed that LOXL4 expression was also increased at both mRNA and protein levels in HCC. Furthermore, we found that LOXL4 upregulation was significantly correlated with tumor differentiation, vascular invasion, and TNM stage and predicted a poor prognosis, in contrast to a previous study demonstrating that LOXL4 is downregulated in HCC tissues, and the downregulation is correlated with aggressive tumors and a worse clinical outcome [12].…”
Section: Discussionsupporting
confidence: 52%
“…Several limitations of the present study should be acknowledged. Firstly, the study was retrospectively designed, although the results were in accordance with previous studies (28,38). Secondly, we only assessed the mRNA expression.…”
Section: Discussionmentioning
confidence: 83%
“…It is involved in the progression of tumor progression and metastasis (31,49,(51)(52)(53). Upregulated expression of LOXL2 has been revealed in several types of cancer, including HCC (54). Extracellularly, LOXL2 can catalyze the covalent cross-linkages of collagen and elastin in the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies that have revealed the expression of LOXL2, Snail and FBP1 in human HCC tissues. For example, LOXL2 was revealed to be frequently overexpressed in human HCC and displayed poor prognosis (54,(58)(59)(60). High expression of Snail or decreased expression of FBP1 was correlated with poor outcomes in HCC patients (61)(62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%